Lights, camera, bones - Haines, Carolyn (Haines, Carolyn. Sarah Booth Delaney mystery, 2024)
"Delaney Detective Agency gets a taste of the spotlight when they are called to a case on a movie set in Greenville, MS, right on the Mississippi River. Marlon Brandon, heir to a wealthy and influential political family, has brought a film crew to town to film a drama about the 1927 flood that submerged a great deal of Greenville. Marlon wants the world to know the story of the flood-and the heroic role the Brandon ancestors played in rescuing dozens of local residents from drowning. Or at least that was the plan until he disappeared. If this weren't concerning enough, the situation appears even more dire when a severed foot is discovered in the Mississippi River, and clues indicate that Marlon may have fallen victim to a freak bull shark attack. But as rumors swirl around the Delta about Marlon's motives for making the film, Sarah Booth and Tinkie have to wonder whether a shark is to blame, or an equally ferocious human offender. The show must go on, and Sarah Booth and her crew will have to investigate all manner of creatures, over land and sea, in order to solve the mystery and save the day"--